Structurally identical capsular polysaccharide expressed by intact Group B Streptococcus versus Streptococcus pneumoniae elicits distinct murine polysaccharide-specific IgG responses in vivo - Arjunaraja, Swadhinya (2012)
We previously reported distinct differences in the murine in vivo Ig polysaccharide (PS)-specific responses to intact Streptococcus pneumoniae compared with Neisseria meningitidis, and that in each case, the bacterial sub-capsular domain markedly influences the Ig response to the associated PS. In light of potentially unique contributions of biochemically distinct capsular PS and/or their characteristic attachments to the underlying bacterium, it remains unresolved whether different bacterial sub-capsular domains can exert differential effects on PS-specific Ig responses to distinct bacterial pathogens. In this report, we utilized a mutant strain of group B Streptococcus (S. agalactiae) type III (GBS-III) that expresses desialylated IIIPS, biochemically identical to type 14 capsular PS (PPS14) of Streptococcus pneumoniae (Pn14), in order to directly compare the in vivo PPS14-specific IgG responses to two distinct Gram-positive bacteria. Although both GBS-III and Pn14 elicited relatively rapid primary PPS14-specific IgG responses dependent on CD4+ T cells, B7-dependent costimulation, and CD40/CD40L interactions, only GBS-III induced a highly boosted ICOS-dependent PPS14-specific IgG response following secondary immunization. Of note, priming with Pn14 and boosting with GBS-III, although not isolated PPS14, elicited a similar boosted PPS14-specific IgG response that was dependent on CD4+ T cells during secondary immunization, indicating that Pn14 primes for memory but, unlike GBS-III, fails to elicit it. The inability of Pn14 to elicit a boosted PPS14-specific IgG response was overcome by co-immunization with unencapsulated GBS-III. Collectively, these data establish that structurally identical capsular PS expressed by two distinct Gram-positive extracellular bacteria can indeed elicit distinct PS-specific IgG responses in vivo.